(untitled) (Archives of Mechanics - Test, 2008)
We consider families of discrete velocity models with physical collision invariants, and develop algebraic criteria for well-posedness of the linearized kinetic boundary layer problem. Using the obtained criteria we discuss various hierarchies of symmetric discrete velocity models, and calculate analytical and numerical slip coefficients for the representants of the hierarchies.